Meat characteristics of red jungle fowl (Gallus gallus Spadiceus), Malaysian domestic chickens (Gallus gallus Domesticus) and commercial broiler - Idris, Lokman Hakim; Goh, Yong Meng; Sazili, Awis Qurni; Mohamed Mustapha, Noordin; Abu Bakar @ Zakaria, Md Zuki (Universiti Putra Malaysia Press, 2015)
The meat characteristics of Red jungle fowl (Gallus gallus Spadiceus) and Malaysian Domestic chicken (Gallus gallus Domesticus), which are known as slow growing birds, were studied. Results were compared with those of the commercial broilers (ROSS) which are fast growing birds. The objective of the study is to determine the meat characteristics (pH, muscle fibre diameter and collagen content) of the breeds and the correlation to their meat quality. For this purpose, a total of 90 chickens (30 chickens for each breed) were used in this study. The chickens in each group were sacrificed at 20, 56 and 120 days posthatching. Findings indicated that collagen content, pH, cooking loss and shear force values in Red jungle fowl and Malaysian Domestic chicken were significantly higher P<0.05) than the commercial broilers. The smaller muscle fibre diameters and lower glycogen reserved contributed to higher pH. Meanwhile, the collagen content showed significantly (P<0.05) positive correlation to shear force and more prominent factors than the size of muscle fibre that determines tenderness of the meat. The commercial broilers’ meat is much tender than that of the Malaysia Domestic chicken and Red jungle fowl.